2010
DOI: 10.1111/j.1537-2995.2010.02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis of red blood cells after cell washing with different automated technologies: clinical implications in a neonatal cardiac surgery population

Abstract: Hemolysis levels vary among different cell washers. Decreasing the expiration time of units after washing may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 30 publications
6
44
0
Order By: Relevance
“…Washed red blood cell concentrates are recommended for large-volume transfusions to potassium-sensitive patients, particularly neonates when fresh units are not available [304], for recipients who have a history of plasma-related transfusion reactions [305], and for the prevention of transfusion-related acute lung injury [306]. Recently, the use of washed RCCs has been proposed as a means to mitigate the accumulation of proinflammatory cells and molecules in stored RCCs to reduce the bioactivity of the product [307] and may be an effective means to address RBC degradation during storage.…”
Section: Overview: Quality Assessment Of Stored Red Cell Concentratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Washed red blood cell concentrates are recommended for large-volume transfusions to potassium-sensitive patients, particularly neonates when fresh units are not available [304], for recipients who have a history of plasma-related transfusion reactions [305], and for the prevention of transfusion-related acute lung injury [306]. Recently, the use of washed RCCs has been proposed as a means to mitigate the accumulation of proinflammatory cells and molecules in stored RCCs to reduce the bioactivity of the product [307] and may be an effective means to address RBC degradation during storage.…”
Section: Overview: Quality Assessment Of Stored Red Cell Concentratesmentioning
confidence: 99%
“…RCCs can be washed in the blood bank using manual centrifugation and extraction methods, semiautomated cell processors, or just prior to transfusion using cell salvage devices [304, 308310]. Manual washing and use of open cell processors hamper widespread use of washed RBCs as the resulting washed products have a limited storage duration.…”
Section: Overview: Quality Assessment Of Stored Red Cell Concentratesmentioning
confidence: 99%
“…The difference in in vivo recovery is not known; however, these modified products have been available for use since 2013. Overall, deglycerolization with the COBE 2991 impacts RBC hemolysis, as seen in previous studies [25,26]. It is also worth noting that this technology produces products in an open system, and the resulting products are limited by a 24-hour outdate.…”
Section: Discussionmentioning
confidence: 77%
“…However, this has been shown to induce some haemolysis, both at the time of processing and (when stored in vitro) for some hours afterwards [13]. A study using RBCs up to 49 days old also found that processing with a cell-saver reduced the toxicity of the suspension fluid, and that some haemolysis occurred, but the number of bags of RBCs was smaller than in the present study, and the authors did not measure the fraction of RBCs that survived [14].…”
Section: Discussionmentioning
confidence: 99%